Prevalence, repairs and complications of hypospadias: An Australian population-based study - Schneuer, F.; Holland, A.; Pereira, Gavin; Bower, C.; Nassar, N. (BMJ Publishing Group, 2015)
© 2015 BMJ Publishing Group Ltd & Royal College of Paediatrics and Child Health. All rights reserved. Objective To investigate hypospadias' prevalence and trends, rate of surgical repairs and post-repair complications in an Australian population. Methods Hypospadias cases were identified from all live-born infants in New South Wales, Australia, during the period 2001-2010, using routinely collected birth and hospital data. Prevalence, trends, surgical procedures or repairs, hospital admissions and complications following surgery were evaluated. Risk factors for reoperation and complications were assessed using multivariate logistic regression. Results There were 3186 boys with hypospadias in 2001-2010. Overall prevalence was 35.1 per 10 000 live births and remained constant during the study period. Proportions of anterior, middle, proximal and unspecified hypospadias were 41.3%, 26.2%, 5.8% and 26.6%, respectively. Surgical procedures were performed in 1945 boys (61%), with 1718 primary repairs. The overall post-surgery complication rate involving fistulas or strictures was 13%, but higher (33%) for proximal cases. Complications occurred after 1 year post-repair in 52.3% of cases and up to 5 years. Boys with proximal or middle hypospadias were at increased risk of reoperation or complications, but age at primary repair did not affect the outcome. Conclusion One in 285 infants were affected with hypospadias, 60% required surgical repair or correction and one in eight experienced complications. The frequency of late complications would suggest that clinical review should be maintained for >1 year post-repair.